2018
DOI: 10.1007/s10571-018-0609-2
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Blood Brain Barrier Disruption by Different Types of Bacteria, and Bacterial–Host Interactions Facilitate the Bacterial Pathogen Invading the Brain

Abstract: This review aims to elucidate the different mechanisms of blood brain barrier (BBB) disruption that may occur due to invasion by different types of bacteria, as well as to show the bacteria-host interactions that assist the bacterial pathogen in invading the brain. For example, platelet-activating factor receptor (PAFR) is responsible for brain invasion during the adhesion of pneumococci to brain endothelial cells, which might lead to brain invasion. Additionally, the major adhesin of the pneumococcal pilus-1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
96
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(98 citation statements)
references
References 186 publications
1
96
0
1
Order By: Relevance
“…The alteration of intercellular tight junction is widely recognized as an important hallmark in meningitic bacterial induction of the BBB disruption, which could be mediated by a direct regulation of the tight junction proteins, as well as by an indirect inflammatory response-mediated tight junction damage [35][36][37][38][39]. However, interestingly, we demonstrated in this work that meningitic E. coli-caused ANGPTL4 induction of BBB disruption depended neither on direct damage of the tight junction proteins by ANGPTL4, nor the ANGPTL4-mediated proinflammatory cytokines production-by the demonstrations that all canonical tight junction proteins like ZO-1, Claudin 5, Occludin; the proinflammatory cytokines involving in BBB disruption like IFN-γ, IL-1β, TNF-α, IL-6, IL-8 [35,39]; as well as the potential endothelial activation markers like EGR-1, E-selectin, ICAM-1, and VEGFA were actually not affected in response to ANGPTL4 treatment or overexpression, which suggested that there might be a novel mechanism of ANGPTL4-mediated BBB disruption during meningitic E. coli infection process. Thus, here comes the question of how ANGPTL4 affects the barrier function of cells.…”
Section: Discussionmentioning
confidence: 99%
“…The alteration of intercellular tight junction is widely recognized as an important hallmark in meningitic bacterial induction of the BBB disruption, which could be mediated by a direct regulation of the tight junction proteins, as well as by an indirect inflammatory response-mediated tight junction damage [35][36][37][38][39]. However, interestingly, we demonstrated in this work that meningitic E. coli-caused ANGPTL4 induction of BBB disruption depended neither on direct damage of the tight junction proteins by ANGPTL4, nor the ANGPTL4-mediated proinflammatory cytokines production-by the demonstrations that all canonical tight junction proteins like ZO-1, Claudin 5, Occludin; the proinflammatory cytokines involving in BBB disruption like IFN-γ, IL-1β, TNF-α, IL-6, IL-8 [35,39]; as well as the potential endothelial activation markers like EGR-1, E-selectin, ICAM-1, and VEGFA were actually not affected in response to ANGPTL4 treatment or overexpression, which suggested that there might be a novel mechanism of ANGPTL4-mediated BBB disruption during meningitic E. coli infection process. Thus, here comes the question of how ANGPTL4 affects the barrier function of cells.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence showing that these molecules reach or influence the CNS via the systemic circulation or neuronal paths. To reach the CNS, inflammatory cytokines have to cross the hematoencephalic barrier, which they can achieve in different ways such as modifying its permeability [58], binding to hematoencephalic barrier-free areas like circumentricular organs, passing through fenestrated capillaries, or using specific carriers [59].…”
Section: Inflammatory Theorymentioning
confidence: 99%
“…Alzheimer's disease pathogenesis involves different bacterial species, like Chlamydia pneumoniae, Helicobacter pylori, and spirochetes [58,65]. These bacteria have been found in different anatomical sections of the CNS, but their primary etiological role in the onset of Alzheimer's disease is still being discussed, even if more evidence about their ability to invade the CNS and interfere with the basic mechanisms of the disease are coming to light.…”
Section: Inflammatory Theorymentioning
confidence: 99%
“… 5 Accumulating evidence has suggested that meningitic pathogens enhance BBB permeability by degrading TJ proteins and that infection-induced neuroinflammatory responses largely aggravate CNS dysfunction. 6 , 7 Meanwhile, several host factors, such as transforming growth factor β1 (TGF-β1), matrix metallopeptidases (MMPs), and vascular endothelial growth factor A (VEGFA) are involved in the regulation of BBB permeability. 8 , 9 , 10 The identification of the key molecules involved in BBB disruption induced by different CNS-infecting bacteria is of great significance; however, the underlying mechanisms by which these key factors regulate BBB permeability in response to infection remain largely unclear.…”
Section: Introductionmentioning
confidence: 99%